IMPLEMENTASI PENDIDIKAN KARAKTER BERBASIS KELAS PADA PEMBELAJARAN IPA OLEH GURU KELAS III A SD NEGERI 036 KARYA INDAH KABUPATEN KAMPAR - Neneng Setiawati; Mahmud Alpusari; Syahrilfuddin Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is a qualitative descriptive research that aims to describe the implementation of character-based educational class on science learning by teacher class III A Elementary School 036 Karya Indah Kampar Regency. This is based on Law No. 20 of 2003 and the character of students in class III A Elementary School 036 Karya Indah Kampar Regency has diversities among hyperactive students, quiet and there are students who have shortcomings in understanding learning and how teachers process the science learning so it can develop the diverse student characters. The data analysis technique used is a qualitative analysis technique that is by describing the research result descriptively in the form of learning process conducted by the teacher. The character that many developed through the learning process is confident with average percentage of appearance 40.5%. The next character that many teachers develop is discipline with an average appearance 24.7%. Other characters developed are tolerance with average percentage of appearance 17.9%, mutual cooperation with average percentage of appearance 6%, honest character with average percentage of appearance 5.1% and responsibility 5.5%. In the process of learning there are different stages of character development such as honest character and responsibility are developed in the core activities and the end of learning. Tolerance character and mutual cooperation are developed in the core activities of learning, as well as the discipline character and confidence are developed in the early activities, core and the end of learning.Keywords: Implementation Of Character , Character-Based Educational Class, Science Learning